ANALISIS PERENCANAAN JEMBATAN KULAN KAMPAK KOTA PANGKALPINANG (BANGUNAN BAWAH DAN BANGUNAN ATAS) - Ramadhan, Kiagus Ahmad Wildan; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The Kulan Kampak Bridge in Pangkalpinang City is planned to replace an old community-built bridge that no longer meets the increasing demands of traffic flow, regional connectivity, and access to key destinations such as the University of Bangka Belitung and local tourism areas. This study aims to analyze the design of the bridge’s superstructure, substructure, and foundation in accordance with technical standards SNI 1725:2016, SNI 2833:2016, and Bina Marga guidelines. The methodology includes field data collection, literature review, load calculation, structural analysis, and design verification for strength, stability, and safety. The superstructure is designed using reinforced concrete T-girders with a total width of 7 m, while the substructure consists of a wall-type abutment. The foundation employs pile foundations based on cone penetration test (CPT) data, with hard soil layers found at depths of 10–14 m. The calculation results indicate that all structural elements meet the required strength, stability, and 50-year design life. This research produces a technical design that can serve as a reference for bridge construction, expected to improve connectivity, support economic activities, and enhance sustainable transportation in Pangkalpinang City. Keywords : Bridge Design, Superstructure, Substructure, Pile Foundation